Food Neophobia and Two Facets of Orthorexia Among Women: Cross-Sectional Study - Tuba Yalçın; Seda Çiftçi; Elif Esra Ozturk (Behavioral Sciences)
The purpose of this study was to investigate the link between food neophobia and two dimensions of orthorexia in women. This cross-sectional study of 985 women aged 18 years and over was conducted using face-to-face questionnaires. Women who had a disability, had a chronic disease, or were pregnant or breastfeeding were excluded. Participants provided information on their sociodemographic details (age and educational level) and frequency of physical activity. Orthorexic tendencies were assessed using the Teruel Orthorexia Scale. The women’s attitude towards trying new foods was assessed using the Food Neophobia Scale. A total of 337 participants (34.2%) were neophilic, 322 participants (32.7%) were neutral, and 326 participants (33.1%) were neophobic. There was no correlation between food neophobia scores and either age or body mass index. However, food neophobia was positively correlated with healthy orthorexia and orthorexia nervosa (p < 0.05). The mean individual scores for orthorexia nervosa and healthy orthorexia according to the Teruel Orthorexia Scale were 11.45 ± 3.91 and 20.04 ± 4.31, respectively. The results indicate that individuals with orthorexia nervosa have higher food neophobia scores, reflecting a greater reluctance to try unfamiliar foods, whereas individuals with healthy orthorexia do not show significant differences in food neophobia tendencies. This distinction highlights the importance of distinguishing between pathological and non-pathological eating behaviors when addressing dietary concerns.